Complications of total implantable access ports and efficacy of Taurolidine-citrate lock solution against catheter-related infections - Emine Ince; Pelin Oğuzkurt; Abdulkerim Temiz; Semire Serin Ezer; Hasan Özkan Gezer; Nalan Yazici; Akgün Hiçsönmez (Wolters Kluwer Medknow Publications, 2014)
Background: Totally, implantable access ports (TIAPs) are used for long standing venous catheterization. This study was designed to present our experiences of the TIAPs applications and efficacy of Taurolidine-citrate lock solution (TCLS) against catheter-related infections. Materials and Methods: We evaluated records of the 108 patients implanted with 112 TIAPs, which had been performed using heparin solution or TCLS between 2005 and 2013. Results: Duration of exposure to TIAPs was 17-2051 days (median: 411 days). The primary diagnoses were solid tumours (n = 57), lymphoma (n = 23), haematologic diseases (n = 23), nephrotic syndrome (n = 4), Hirschsprung disease (n = 1). The right external jugular vein was most frequently used vascular access route (72.3%). Mechanical complications were observed in four cases. TIAPs were removed due to remission in 19 cases and infection in 19 cases. Median time from implantation and to the development of infection was 60 days. Heparin solution had been used for care in 33 ports, whereas heparin and TCLS had been used in 79 ports. Based on statistical comparison, use of TCLS was considered to be an important factor for preventing infection (P = 0.03). Conclusion: We consider that TCLS reduces infection prevalence so TIAPs would be used more extensively and effectively to prevent infections.